The control of merit front to audits “3E” of the General Office of the Republic - Muñoz Cid, Manuel Ángel (Derecho Público Iberoamericano, 2017)
The control is a key element for a Constitutional state, since it supposes limiting the public power. But the discretionary legal authorities are qualified as matters of merit, convenience or opportunity, in order to exempt them of the control. In this context, the approach of control “3E” of the Contraloría General de la República aspires to overcome these problems, being still the model of other entities worldwide.